EFEKTIVITAS DAN KEBERLANJUTAN PEMBIAYAAN LASISMA SEBAGAI INSTRUMEN TRANSFORMASI DALAM MENDORONG INKLUSI KEUANGAN SYARIAH - Fawaid Fawaid; Muhammad Amin Saifullah; M. Faris hidayat Tuloh; Moh. Ishomuddin A.M (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2025)
Sharia financial inclusion through the LASISMA scheme is an important instrument in expanding access to fair and sustainable financing for MSMEs. This study aims to evaluate the effectiveness of LASISMA financing in enhancing Islamic financial inclusion at BMT NU East Java, Jambesari Branch, with a focus on implementation strategies, challenges, and its impact on MSMEs. This research employs a qualitative method with a case study approach through interviews, observations, and documentation. The findings reveal that LASISMA proven to be effective in helping MSME actors access Islamic financing, grow their businesses, and build economic independence. However, there are still challenges such as limited funding, lack of human resources, and low Islamic financial literacy. LASISMA financing plays a significant role in promoting Islamic financial inclusion, but institutional strengthening and more intensive assistance are needed to ensure the program runs more optimally and sustainably. Keywords : Effectiveness of Islamic Financing, Sustainability of LASISMA, Islamic Financial Inclusion